Fiscal Foresight and Perverse Distortions to Firm Behavior: Anticipatory Dips and Compensating Rebounds - Robert S. Chirinko; Daniel J. Wilson (Center for Economic Studies and ifo Institute (CESifo), 2023)
We study the conditions under which fiscal foresight – forward-looking agents anticipating future policy changes – results in perverse economic behavior through unintended intertemporal tradeoffs. Somewhat surprisingly, fiscal foresight by itself is far from sufficient for policy-induced incentives to perversely distort firm behavior. Rather, we show that there are two additional sets of conditions, at least one of which must hold to generate perverse behavior: (i) storable output, diminishing returns, and a non-competitive output market; (ii) "rolling base" policy design and storable output. These conditions suggest that the estimated impacts of fiscal policies may be sensitive to underlying economic or legislative characteristics and that policies targeted to specific firms or industries with unique characteristics may not be generalizable.
Keywords: E62; H20; 330; fiscal foresight; intertemporal tradeoffs; real distortions; fiscal policy